The WiFeS Ionized Gas Kinematics of the Edge-on Galaxy J1447-17 - Mputle, Omphemetse Kelebogile (Department of Astronomy, 2022)
The presence of extraplanar diffuse ionized gas (eDIG) and galactic winds and outflows in the late Universe has been observed to be ubiquitous in nearby star-forming spiral galaxies. Optical integral field spectroscopic data from the Wide Field Spectrograph (WiFeS) on the 2.3m Australian National University Telescope is used to determine if the nearby edge-on galaxy J1447-17 from the SINGG survey hosts eDIG, winds or outflows. Tests used to detect their existence include the presence of multiple components in the Hα signal, an increased velocity dispersion in the off-plane region relative to the disk, residuals in the velocity asymmetry map and an enhanced line-ratio ([N II]λ6583/Hα) corresponding to a decrease in the Hα intensity in the case of eDIG. The absence of profiles meeting the line-ratio condition and absence of multiple Hα components compounded with strong residuals in the velocity asymmetry map are not indicative of the galaxy possessing diffuse ionized gas. Ionization cone signatures in the velocity dispersion map together with the velocity asymmetry map and greater dispersion in the off-plane regions than in the disk indicate that the galaxy hosts a galactic wind.